A comparative study of simple geometrical head phantoms on specific absorption rates for simulations and measurements at 900MHz - Mohd Hafizuddin, Mat; Mohd Fareq, Abd Malek, Dr.; Ronald, Suzanna Harun; Zulkefli, M. S. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/